Evaluation of a social network intervention on child feeding practices and caregiver knowledge. Issue 3 (1st April 2019) - Fiorella, Kathryn J.; Gavenus, Erika R.; Milner, Erin M.; Moore, Megan; Wilson‐Anumudu, Folasade; Adhiambo, Florida; Mattah, Brian; Bukusi, Elizabeth; Fernald, Lia C. H.
Abstract: Food insecurity and poor infant and young child feeding (IYCF) practices contribute to undernutrition. The Kanyakla Nutrition Program was developed in rural Kenya to provide knowledge alongside social support for recommended IYCF practices. Utilizing a social network approach, the Kanyakla Nutrition Program trained community health workers (CHWs) to engage mothers, fathers, and grandparents in nutrition education and discussions about strategies to provide instrumental, emotional, and information support within their community. The 12‐week programme included six sessions and was implemented on Mfangano Island, Kenya, in 2014–2015. We analysed intervention effects on (a) nutrition knowledge among community members or CHWs and (2) IYCF practices among children 1–3 years. Nutrition knowledge was assessed using a postintervention comparison among intervention (community, n = 43; CHW, n = 22) and comparison groups (community, n = 149; CHW, n = 64). We used a quasi‐experimental design and difference‐in‐difference to assess IYCF indicators using dietary recall data from an ongoing cohort study among intervention participants ( n = 48) with individuals living on Mfangano Island where the intervention was not implemented ( n = 178) before the intervention, within 1 month postintervention, and 6 months postintervention. Findings showed no effect of the intervention on IYCF indicators (e.g., dietary diversity and meal frequency), and less than 15% of children met minimum acceptable diet criteria at any time point. However, knowledge and confidence among community members and CHWs were significantly higher 2 years postintervention. Thus, a social network approach had an enduring effect on nutrition knowledge, but no effects on improved IYCF practices. Abstract :